Feature. (November 2018) - Myburgh, Hanlie; Calitz, Esmé; Railton, Jean P.; Maluleke, Christina; Mashao, Elizabeth; Ketelo, Patiswa; Jobson, Geoff; Grobbelaar, Cornelius J.; Struthers, Helen E.; Peters, Remco P.H.
Abstract : N/A: Disclosing to a child that s/he is living with HIV is necessary to promote adherence to treatment and improve health outcomes. Facilitating disclosure between caregivers and children remains a challenge for health workers. Understanding how health workers are involved in and perceive the disclosure process is integral to engaging with such challenges. We held group discussions with and surveyed 73 physicians, nurses, and counselors across 16 randomly selected facilities in two rural South African health districts, exploring their experiences of supporting disclosure between caregivers and children. Ninety percent of those surveyed agreed that children should be informed of their HIV status. Differences between categories of health workers regarding training, involvement in the disclosure process, and perceived responsibility for disclosure support led to inconsistent disclosure practices within facilities. Disclosure‐strengthening interventions must consider the composition of the health worker team and the role that each category of health worker performs in their local settings.